Teachers' Global Perceptions and Views, Practices and Needs in Multicultural Settings - Zoe Karanikola; Glykeria Katsiouli; Nektaria Palaiologou (MDPI AG, 2022)
Multiculturalism and globalization are common traits of western societies, and affect the way people interact and communicate. In such a context, this study comes to investigate teachers' perceptions, practices and needs towards global and intercultural competences. This study was designed and implemented in order to shed light on major issues which are associated with the context of global competences as an umbrella term, which arose during the researchers' participation at an Erasmus plus European project. The research took place at the region of Attica and thirteen teachers (N = 13) of reception classes-Zones of Educational Priority (ZEP)-participated in the interview. A qualitative case study followed, focusing on a specific geographic region, and the semi-structured interview tool was used. The findings of the research indicate that educators do not feel certain about the differences between global and intercultural competences. However, they consider that these competences are of great importance and they recognize the contribution of schools to their development. Regarding their practices, they mostly refer to the dialogue and discussion techniques, the role playing, and the project-based teaching. Finally, participants consider that they are not sufficiently prepared to teach global and intercultural competences. Thus, participation in relevant training programs is important.